Efektivitas infusa daun kalakai (Stenochlaena palustris (Burm.F) Bedd) terhadap kadar kolesterol total pada tikus putih galur wistar yang diinduksi CCl4 - Saloh, Rachel Sarita; Carmelita, Austin Bertilova; Nugrahini, Sintha; Balyas, Abi Bakring; Adnyana, I Gde Hary Eka (Barigas: Jurnal Riset Mahasiswa, 2024)
Cholesterol can be attacked by CCl4 by increasing lipid peroxidation, where CCl4 causes an increase in acetate transport into the liver, resulting in an increase in substrate (acetate) which causes cholesterol synthesis to also increase. Based on previous research, the kalakai plant (Stenochlaena palustris (Burm.F) Bedd) has good antioxidants to ward off free radicals. Objective: To determine the potential of kalakai leaf infusion to prevent the increase in total cholesterol levels induced by CCl4. Method: True experimental research with a post test only control group design, using 24 white male Wistar rats weighing 200-250 g, divided into three treatment groups and a negative (-) group induced by CCl4. Treatment groups I, II, II were given kalakai leaf infusion at a dose of 300 mg/kgBW, 400 mg/kgBW, 500 mg/kgBW. This research was conducted for 15 days. Research Results: In the normality and homogeneity test, the sig>0.05 value was obtained, so it can be concluded that the data is normally and homogeneously distributed. Then the data can be continued for Oneway ANOVA hypothesis testing, and a value of sig>0.05 is obtained. Based on the research results, there was no effect from the kalakai leaf infusion and the hypothesis was rejected.